Apa "Apa yang Kita Hadapi Selama Pembelajaran WhatsApp": Menyuarakan Pendapat Siswa di Masa Pandemi Covid-19 - Fiki Nailil Mursyida; Dewi Puspitasari (Dinamika Bahasa dan Budaya, 2023)
The aim of this study is to present a summary and an overview of students’ experience using WhatsApp Group as a learning tool during Covid-19 pandemic based on Gregory’s theory by using narrative inquiry method. Students frequently use WhatsApp, a message-sharing social media application, to collaborate on schoolwork. This research involved the 4th semester students from the English Department in UIN KH Abdurrahman Wahid Pekalongan. The researchers conducted data collection through online and offline interviews which were carried out via WhatsApp and face-to-face interview. The data was then categorized in accordance with the theme by Braun and Clarke. This research concentrated on how students experienced learning through WhatsApp Group. Based on the data obtained through interviews, the results lead to the positive experiences and negative experiences. Four out of five students categorized the experiences into negative one because they faced more obstacles than improvements. Therefore, the results from this data are more dominant to negative experience such as WhatsApp Group did not facilitate students’ learning comprehension, Internet connection became problems in certain areas, the WhatsApp Group tended to be boring, and students lacked of teacher’s supervision thus they had to understand the materials themselves. Keywords: experience, negative experience, positive experience, WhatsApp Group, learning tool